New Case of Chagas Disease in Sihuas Valley, Arequipa - Cornejo Donayre, Alberto (1960)
For several years we are conducting research in conjunction with clinical and epidemiological aspect of the disease do in Peru, in order to obtain information on the magnitude of this problem is between us. Studies by Escomel (6), 1917; Ayulo and Herrera in 1944 (1) (7); Donayre Lumbreras C. Cornejo and in 1950-1951 (2) (3) (4); C. Lumbreras in 1952 (9); Taboada and García Lazo Durand in 1953 (8); Montesinos, Náquira and others in 1956 (10) 1958 And lately we (5) have shown that the American Trypanosomiasis is endemic in the main valleys of the department of Arequipa.